Learning and unlearning sexism in the workplace. Issue 5 (13th July 2015) - Jeffrey, Heather L; Beswick, Esme; Meade, Jessica
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Looks at the barriers that prevent women achieving equality in the workplace and examines how they may be overcome. Design/methodology/approach – Argues that there are two potentially important barriers to creating a more inclusive workplace: Employees may conform to discriminatory practices even though they do not really agree with them just to fit in, and overly competitive environments can create a situation whereby employees are afraid to speak out. Findings – Suggests that, in order to tackle these barriers, employers and managers at all levels must call upon insight, use fair judgment and communicate with their female staff to increase understanding of what may be perceived as sexist. Practical implications – Urges managers to create a safe space for women to speak out against discrimination as, even though the organization may be aiming at creating an ethical environment, there may be situations that go unnoticed. Social implications – Suggests that the working environment may also affect relationships between employees, creating a situation where they may not feel able to speak out. Originality/value – Advances the view that managers must use insight and call upon female experience in order to create a more equal environment.